2017
DOI: 10.1111/ped.13260
|View full text |Cite
|
Sign up to set email alerts
|

Social independence of adult congenital heart disease patients in Japan

Abstract: Because financial issues can adversely affect the psychological profiles of adult CHD patients, enhancement of social welfare and employment support may improve their social independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Of those who were employed, less than half (48%) were working full time. Many subjects in this study pointed out the need for understanding in the workplace, as well as employment and financial support 40 . It was also reported that employment, quality of life, and patient satisfaction are related in patients with congenital heart disease 41 .…”
Section: Transition From Pediatric To Adult Social and Welfare Servicesmentioning
confidence: 71%
See 1 more Smart Citation
“…Of those who were employed, less than half (48%) were working full time. Many subjects in this study pointed out the need for understanding in the workplace, as well as employment and financial support 40 . It was also reported that employment, quality of life, and patient satisfaction are related in patients with congenital heart disease 41 .…”
Section: Transition From Pediatric To Adult Social and Welfare Servicesmentioning
confidence: 71%
“…Many subjects in this study pointed out the need for understanding in the workplace, as well as employment and financial support. 40 It was also reported that employment, quality of life, and patient satisfaction are related in patients with congenital heart disease. 41 From these results, it is ideal for ACHD patients to be able to fully reach their potential, contribute to society, and secure an income.…”
Section: Transfer Of the Patientsmentioning
confidence: 98%
“…2,3,[8][9][10][11] Conversely, use of private health insurance, peers' awareness and understanding of CHD and its impact in the workplace, and employer accommodations for physical restrictions can facilitate increased employment for adults with CHD. 8,[10][11][12][13][14] Currently, our knowledge of employment among adults with CHD includes data from clinical registries, single-centre retrospective reviews, and cross-sectional surveys. [3][4][5][6]15 However, these studies have been limited by small sample sizes (in single-centre reviews and crosssectional surveys), a bias towards including only patients followed by a cardiology service, and lack of generalisability to United States employment and health care systems (among studies conducted using European population-based registries).…”
mentioning
confidence: 99%